2014
DOI: 10.3174/ajnr.a3961
|View full text |Cite
|
Sign up to set email alerts
|

Hyperintense Basilar Artery on FLAIR MR Imaging: Diagnostic Accuracy and Clinical Impact in Patients with Acute Brain Stem Stroke

Abstract: BACKGROUND AND PURPOSE: FLAIR-hyperintense vessels are known to be a sign of sluggish collateral blood flow in hemispheric vessel occlusion. Additionally, they seem to have a prognostic implication. The aim of the current study was to evaluate the hyperintense configuration of the basilar artery (FLAIR-hyperintense basilar artery) as a marker of basilar artery occlusion and as a predictor of patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Two studies showed that proximal basilar occlusions are more likely unfavorable predictors of outcome compared to distal occlusions (13, 29). This is consistent with a prior catheter cerebral angiography-based study of 22 patients who evaluated predictors of survival and good neurological outcome in patients treated with basilar artery thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed that proximal basilar occlusions are more likely unfavorable predictors of outcome compared to distal occlusions (13, 29). This is consistent with a prior catheter cerebral angiography-based study of 22 patients who evaluated predictors of survival and good neurological outcome in patients treated with basilar artery thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion site was also found to be a predictor of patient outcome. All patients with occlusion of the proximal basilar artery died, compared to 82% survival rates with occlusion in the mid-basilar section and 100% survival with thrombus at the basilar tip (23). …”
Section: Thrombus Burden and Locationmentioning
confidence: 99%
“…Signal changes from the blood clot itself, perhaps reflecting an effect of oxyhemoglobin, may also contribute to this imaging manifestation [24]. One study addressing basilar artery occlusion showed that the length of FLAIR hyperintensity within the vessel directly correlated with poorer prognosis [24]. Hyperintensity of hepatic hemangiomas on FLAIR sequences has also been used to distinguish these lesions from cysts and also presumably reflecting slow flow within these vascular collections [25].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have also demonstrated that hyperintense vessels on FLAIR sequences may be seen in regions of acute cerebral infarction and are regarded to represent slow blood flow through collateral arterial vasculature, either from occlusion, vasospasm, or stenosis [22,23,24]. Signal changes from the blood clot itself, perhaps reflecting an effect of oxyhemoglobin, may also contribute to this imaging manifestation [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation